Steam pretreatment and enzymatic hydrolysis of Eucalyptus viminalis chips. - Ramos, Luiz Pereira. (University of Ottawa (Canada), 1992)
The steam pretreatment of Eucalyptus viminalis chips was characterized. Pretreatment parameters such as steam temperature, residence time, addition of SO$\sb2$ as an acid catalyst, and initial moisture content of the chips were evaluated in order to optimize recovery, fractionation and enzymatic hydrolysis of pretreated materials. In the absence of an acid catalyst, the best pretreatment was obtained at 230$\sp\circ$C for 120 s using chips with a moisture content of 50% (w/w). Pretreatment by steam explosion showed no variation resulting from differences in the initial moisture content of the chips. However, when the substrate was steam-treated without explosion, the initial moisture content of the chips had a significant influence on the recovery yield and the degree of enzymatic hydrolysis. When the chips were impregnated with sulfur dioxide (1% SO$\sb2$, w/w) prior to steaming, milder pretreatment conditions of 210$\sp\circ$C for 50 s were sufficient because of the catalytic action of the SO$\sb2$ gas. SO$\sb2$ catalysis was shown to be particularly beneficial for the steam explosion of green chips. More than 95% of the original cellulose could be hydrolysed to glucose with more than 90% of the original pentosan recovered as xylose in the water-soluble fraction. It appeared that the efficient uptake of the SO$\sb2$ catalyst was dependent on the initial moisture content of the chips. Enzymatic hydrolysis of SO$\sb2$-impregnated, steam-treated E. viminalis was carried out with increasing substrate concentrations and enzyme loadings. Removal of the alkali-soluble lignin had a minor effect on the hydrolysis yield when both the substrate concentration and enzyme loading were calculated in relation to the cellulose content. The mode of action of Trichoderma cellulases was further investigated by looking at changes which occurred in the morphology and fine structure of the cellulosic substrate during hydrolysis. A rapid reduction in fiber length (fragmentation), followed by an almost complete saccharification of cellulose, was observed for several fractions derived from pretreated eucalyptus. A gradual decrease in the degree of polymerisation (DP) of the SO$\sb2$-SEE-WIA/$\rm H\sb2O\sb2$ fraction reflected the high susceptibility of this substrate to hydrolysis. However, when the influence of hydrolysis on the DP of a fully bleached kraft pulp derived from eucalyptus was investigated, there was no noticeable change in the DP distribution of the residue until 24 h of hydrolysis. It seemed that the mode of action of Trichoderma cellulases varied depending on the type of pretreated substrate that was hydrolysed. As hydrolysis resulted in a gradual decrease in both the degree of polymerisation (DP) and the degree of crystallinity of the F-150 fraction, it was apparent that the depolymerisation of this substrate was predominantly due to exoglucanase activity. By contrast, the enzymatic hydrolysis of the FBEP-48 fraction resulted in little change in either the cellulose DP or the degree of crystallinity of the substrate. This suggested a "peeling off" type of mechanism. The susceptibility of the pretreated substrates to enzymatic hydrolysis could not be easily predicted from the differences in their cellulose DP or crystallinity. (Abstract shortened by UMI.)
Keywords: Engineering, Chemical.